Integrated analysis reveals common DNA methylation patterns of alcohol-associated cancers: A pan-cancer analysis - Liu, Xingyu; Chen, Jiarui; Li, Jiali; Zeng, Zihang; Jiang, Xueping; Gao, Yanping; Huang, Zhengrong; Wu, Qiuji; Gong, Yan; Xie, Conghua (Frontiers in Genetics, 2023)
Background: The role of alcohol in carcinogenesis has received increasing attention in recent years. Evidence shows its impacts in various aspects, including epigenetics alteration. The DNA methylation patterns underlying alcohol-associated cancers are not fully understood. Methods: We investigated the aberrant DNA methylation patterns in 4 alcohol-associated cancers based on the Illumina Human Methylation450 BeadChip. Pearson coefficient correlations were identified between differential methylated CpG probes and annotated genes. Transcriptional factor motifs were enriched and clustered using MEME suite, and a regulatory network was constructed. Results: In each cancer, differential methylated probes (DMPs) were identified, and 172 hyper- and 21 hypo-methylated pan-cancer DMPs were examined further. Annotated genes significantly regulated by PDMPs were investigated and enriched in transcriptional misregulation in cancers. CpG island chr19:58220189-58220517 was hypermethylated in all 4 cancers and silenced in transcription factor ZNF154. Various biological effects were exerted by 33 hyper- and 7 hypomethylated transcriptional factor motifs grouped into 5 clusters. Eleven pan-cancer DMPs were identified to be associated with clinical outcomes in the 4 alcohol-associated cancers, which might provide a potential point of view for clinical outcome prediction. Conclusion: This study provides an integrated insight into DNA methylation patterns in alcohol-associated cancers, and reveals the corresponding features, influences, and potential mechanisms.